Exchange rate controls and illegal trade in Brazil: a lesson from the 80´s - Marcos C. Holanda (Universidade de São Paulo, 2000)
The coexistence of exchange rate control, a black market for foreign currency and illegal trade has been a common characteristic of developing economies. The paper undertakes an empirical investigation about the interaction between high premia on the black market for the Dollar and illegal trade for the case of Brazilian economy. It develops a new approach to access the size of illegal trade and shows that during the 80s’ illegal trade accounted for a significant portion of Brazilian international transactions.